Power, empowerment and organisational communication - Anna Oksiutycz (Communicare)
Power is an integral part of organisational life. Main schools of thought on the subject of power in an organisational setting consider power to be either a resource held by individuals and departments, or an inherent feature of organisational structure and society. While it is relatively easy to identify surface manifestations of power, the deep structures of power are much more difficult to analyse. Public relations literature focuses on power “held” by public relations practitioners and the power of public relations departments in their relations with other departments in an organisation, as well as the imbalances of power between the organisations and their respective publics. In the context of the increasing complexity of the organisational environment, this article suggests the application of organisational cybernetics to public relations theory, and it considers the role that organisational communication plays in releasing the productive power of employees and in designing effective organisations through the introduction of recursive organisational structures.